Methodology for Studying of Some Basic Parameters in the Granulation Process of Poultry Manure: - Khalil, Elham; Bogomiliov, Boian; Kolev, Bozhidar (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2019)
Analysis of the results of the study: The results of the study of the granulation process of poultry manure are presented in this paper. The correlation between the parameters has been evaluated. The degree of influence of the controllable factors has been determined. Adequate mathematical models of basic process parameters have been derived.